INDICES OF FECUNDITY IN THE HILLSTREAM FISH GARRA MULLYA - Somvanshi, V S (Indian Journal of Fisheries, 2011)
The fecundity of Garra miillya in relation to fish length, fish weight, gonadlength and gonad weight are worked out and equations using regression andmultiple regression analyses are given. The equation on the gonad lengthfecundityrelationship gives more reliable fecundity estimate. The fecundity isdiscussed as a manifestation of aging and as an adaptation to the ecologicalconditions peculiar to the hillstreams, terming this adaptation, together with themorphological adaptations of the fish, as "bioecological adaptation."